Traditional Cantonese puerperal practices and postpartum cardiometabolism in gestational diabetes - Wu, Liting; Pei, Ling; Li, Zeting; Xiao, Huangmeng; Liu, Huiling; Yue, Shufan; Chen, Li; Chen, Wenzhan; Li, Yanbing; Xiao, Haipeng; Cao, Xiaopei (Asia Pacific journal of clinical nutrition, 2022)
Background and Objectives: With gestational diabetes (GDM), women have a higher risk for future type 2 diabetes, and risk factors for diabetes for it are amplified. Whether this phenomenon is affected by traditional puerperal or postpartum practices among Chinese women who develop gestational diabetes is unclear. This has been explored in a Cantonese cultural setting to enable relevant risk management. Methods and Study Design: Some 138 women were followed before, during and after pregnancy in accordance with Cantonese Puerperal Practices (CPP), and occurrence of GDM and exclusive breast-feeding. Body compositional and cardiometabolic information were collected. These included glucose tolerance and insulin resistance. Results: During a median postpartum follow-up of 60.4 days, women with a typical CPP had a greater body weight and weight retention. With artificial feeding, women with a typical CPP had greater OGTT glycemic responses and more insulin resistance. With exclusive breast-feeding, however, no differences in postpartum cardiometabolic measurements were observed, except for a higher early-phase insulin response. Conclusions: Traditional CPP is associated with early postpartum cardiometabolic impairment in gestational diabetes, but this is avoided with breast-feeding.